Global Stability of Almost Periodic Solution of a Class of Neutral-Type BAM Neural Networks - Tetie Pan; Bao Shi; Jian Yuan (Abstract and Applied Analysis)
A class of BAM neural networks with variable coefficients and neutral delays are investigated. By employing fixed-point theorem, the exponential dichotomy, and differential inequality techniques, we obtain some sufficient conditions to insure the existence and globally exponential stability of almost periodic solution. This is the first time to investigate the almost periodic solution of the BAM neutral neural network and the results of this paper are new, and they extend previously known results.